Loss of 24 h rhythm and light-induced c-fos mRNA expression in the suprachiasmatic nucleus of the transgenic hypertensive TGR(mRen2)27 rat and effects on cardiovascular rhythms - Lemmer, Björn; Hauptfleisch, Stefan; Witte, Klaus (Brain research, 2000)
Immediate early genes, especially c-fos, are thought to play an essential role in photic entrainment of circadian rhythms. A special characteristic of the transgenic hypertensive TGR(mRen2)27 rat strain, expressing an additional mouse renin2 gene, is the inverse blood pressure rhythm in relation to those in heart rate and activity resulting in internal desynchronisation of these physiological rhythms. Assessment of c-fos mRNA expression by microdissection and RT-PCR in the suprachiasmatic nucleus showed, that in contrast to normotensive Sprague-Dawley rats the 24 h and circadian rhythm of c-fos mRNA expression in TGR(mRen2)27 rats is abolished. Moreover, light-induced c-fos expression within the nucleus could be found in the normotensive controls, but was absent in transgenic hypertensive rats. The light pulse applied during the subjective night, at CT 14, significantly phase delayed rhythms in blood pressure, heart rate and activity in the normotensive rats by about 2 h, whereas in the transgenic hypertensive animals rhythms in blood pressure and heart rate were unaffected, only activity showed a slight phase shift. In conclusion, these data suggest that the transgene in TGR leads not only to a disturbance of the cardiovascular system but also influences the light entrainment response, which is accompanied by a suppressed c-fos mRNA expression in the suprachiasmatic nucleus.